Wokół etyki niesienia pomocy psychologiczno-pedagogicznej - Dudek, Mieczysław (Annales. Etyka w Życiu Gospodarczym, 2008)
The most basic aim of the psychological and pedagogical advisory centre is providing the childand its family with support at every stage of the problems arising. The target of such centres is alsoundertaking preventive, diagnostic, therapeutic, counselling and advisory actions. The profession ofa diagnostic – therapeutic counsellor triggers ethical dilemma. Two parties meet and interact with eachother in the relations occurring in such advisory centres – the counsellor and the person who needsadvice and help. To enable such a contact and make it effectively therapeutic instead of destructive,specialists employed in these centres have to be not only competent and highly qualified but also shouldpossess a sufficient amount of knowledge about themselves, their system of values, opinions etc.